PERSEPSI SISWA SMA KOTA PAREPARE TENTANG STAIN PAREPARE - Hidayat, Wahyu (Kuriositas: Media Komunikasi Sosial dan Keagamaan, 2016)
Competition is tight in the capture of new students, demanding STAIN Parepare to be able to capture the desired expectations of prospective students. Moreover, it is common knowledge if STAIN still not be a top priority by high school students who would go on to college. Therefore, researcher are interested to see the perception of high school students in Parepare about STAIN Parepare. This research is expected to provide for the STAIN Parepare enter in an effort to increase the number of students. This type of research was a research survey, the number of 216 respondents spread across several at Senior High School in the margin of error of 5%. Cluster sampling technique is random sampling or random system, where the sampling is done by dividing the population based group or cluster area, which is the base School and Education Program (Science and Social Studies). Research using questionnaire instruments and data analysis with quantitative descriptive analysis. Based on the results of the study the majority of the City Parepare SMA (63.47%) still do not know of many STAIN Parepare and 53.11% of high school students consider majors STAIN Parepare only open religion studies, 26.76% of high school students in Parepare never read advertisements / news STAIN Parepare in the local newspaper, Pare Pos, 20% of students see STAIN Parepare appeared on CTV Pare, 14.44%, continuing college students who are interested in Parepare STAIN. 36.53% Students of Parepare think STAIN Parepare as favorite college Parepare. Prodi / computer science an option that has been chosen by high school students in Parepare (34.78%). Prodi Pendidikan Bahasa Inggris (PBI) is still a favorite choice options (48.13%).